China 2030 : building a modern, harmonious, and creative high-income society - World Bank (Washington) (World Bank, 2013)
This report examines whether China's economy can continue to grow to become the world's largest economy, even if its current growth rate slows, and whether it can maintain rapid growth with little disruption to the world, the environment and its own culture.